Inovasi Permen Herbal Sebagai Alternatif Pangan Fungsional Peningkat Nafsu Makan Anak - Nuriyana, Laha; Hidayat, Khoirul; Firmansyah, R. Arief (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2025)
Loss of appetite is a common problem in children. This loss of appetite can lead to health and developmental problems. Loss of appetite is often attributed to internal factors, such as worm infections. Parents often try to increase appetite through vitamins, pharmacological medications, and traditional medicine. However, many children refuse to consume traditional medicines because they have a bitter and unappealing taste. One innovation to encourage children to consume herbal medicine is to process it into candy. This candy is made from spices such as Javanese ginger and roselle. This candy contains curcumin and anthocyanins, which can increase children's appetite. This research aims to develop the best formulation for Javanese ginger herbal candy, using roselle flowers as an additional ingredient, to produce a pink color that children love. The resulting pink color will attract children's attention to consume Javanese ginger candy. This research design used a Completely Randomized Design (CRD) model with variations in the addition of curcuma extract concentrations (6, 8, 10, 10 g) and rosella extract (2, 3, 4, 5 g). The resulting candy was then tested, including water content testing, flavonoid testing, antioxidant testing, solubility testing, curcumin content testing, and pH testing. The addition of curcuma extract and rosella flower extract had a significant effect on water content, antioxidant activity, pH, and curcumin content. The best treatment was treatment F3 with the addition of 10 g of curcuma extract and 4 g of rosella flower extract. The results of the curcumin content test for herbal candy with curcuma extract and rosella flower extract were classified as very low at 0.0020%. This figure is very small in meeting the curcumin levels in children, so it is not effective in increasing children's appetite.